PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA HOTEL THE RITZ CARLTON MEGA KUNINGAN JAKARTA - Nurul Adha Aini; Parlagutan Silitonga (Human Capital Development, 2020)
The purpose of this Research is to determine the direct effect of Compensation on Motivation, Training on Motivation, Compensation on Performance, Training on Performance, as well as Motivation on Performance. Furthermore, this study also aims to determine the indirect effect of Compensation on Performance through Motivation variables and Training on Performance through Motivation variables. This study is using descriptive and quantitative research by conducting surveys based on data through questionnair’s distribution. The research method used is path analysis with employee of The Ritz Carlton Mega Kuningan Hotel, Jakarta as the questionnaire data and the sample consist of 174 respondents by accidental method. The test results shows Compensation and Training have positive and significant effect on Motivation. Likewise, Compensation, Training and Motivation have positive and significant effect on Performance. Moreever, Compensation and Training also have indirect effect on Performance with Motivation as a moderator variable.